Reading the French enlightenment : system and subversion - Hayes, Julie Candler, 1955- (Cambridge studies in French ;, 1999)
Julie Candler Hayes surveys the past fifty years of philosophical reflection on the Enlightenment, and takes issue both with traditional liberal and with contemporary critical accounts. Through close analysis of philosophical, scientific, and literary texts, she emphasizes the urgency of maintaining a dialogue between past and present, Enlightenment and modernity.